CT FINDINGS IN HYPERTENSIVE INTRACRANIAL PARENCHYMA HEMORRHAGE - THANOMKIAT, Wiwatana; PEKANAN, Patchrin; HIRUNPAT, Siriporn; SANGSAI, Achara (The ASEAN Journal of Radiology, 2023)
A retrospective study of the CT scans of the patients with hypertensive intracranial parenchymal bleeding, was performed in 141 patients. Bleeding at the putamen/ external capsule, thalamus, subcortical white matter, cerebellum, brain stem and internal capsule was seen in 42, 26, 12, 10, 9 and 1 percents of cases respectively. The incidence of rupture of the hematoma into the ventricles from the sites mentioned above was 44, 75, 41,43,30 and 0 percents of the total hematomas at each site respectively.